The effectiveness of diorama media and digital archives of Aboriginal tribes loaded with design thinking to strengthen the national identity of history learners - Printina, Brigida Intan; Krisnamurti, Cyrenia Novella; Rusmawan, Rusmawan; Anugrahana, Andri; Utama, Florentinus Galih Adi (Edelweiss Applied Science and Technology, 2025)
The study evaluates the effectiveness of diorama media and Aboriginal digital archives integrated with design thinking in enhancing national identity among history learners. A quantitative experimental survey design was applied to 30 fifth-semester History Education students at Universitas Sanata Dharma, class of 2023, using a 5-point Likert scale questionnaire. Data were analyzed through descriptive statistics, Pearson correlation, and simple linear regression using R software version 4.3.2. Results revealed an average score of 4.42 for Historical/Cultural Visualization, indicating strong agreement that dioramas vividly depict Aboriginal historical events, and 4.34 for Contextual Understanding, reflecting high comprehension of historical material. The Pearson correlation coefficient (, ) confirmed a strong positive relationship between visualization and contextual understanding. Linear regression () indicated that visualization accounts for 54.35% of contextual understanding variance. The design thinking approach, through empathize, define, ideate, prototype, and test stages, fostered emotional engagement and critical analysis, supporting national identity reflection via comparisons with Indonesian cultural diversity. The study supports the hypothesis that these media enhance national identity in the experimental group. Limitations include a small sample size, suggesting future research with larger samples and augmented reality integration.